Impaired free fatty acid utilization by skeletal muscle in non-insulin-dependent diabetes mellitus. - Kelley, D E (1994)
This study was undertaken to assess utilization of FFA by skeletal muscle in patients with non-insulin-dependent diabetes mellitus (NIDDM). 11 NIDDM and 9 nondiabetic subjects were studied using leg balance methods to measure the fractional extraction of [3H]oleate. Limb indirect calorimetry was used to estimate RQ. Percutaneous muscle biopsy samples of vastus lateralis were analyzed for muscle fiber type distribution, capillary density, and metabolic potential as reflected by measurements of the activity of seven muscle enzyme markers of glycolytic and aerobic-oxidative pathways. During postabsorptive conditions, fractional extraction of oleate across the leg was lower in NIDDM subjects (0.31 +/- 0.08 vs. 0.43 +/- 0.10, P < 0.01), and there was reduced oleate uptake across the leg (66 +/- 8 vs. 82 +/- 13 nmol/min, P < 0.01). Postabsorptive leg RQ was increased in NIDDM (0.85 +/- 0.03 vs. 0.77 +/- 0.02, P < 0.01), and rates of lipid oxidation by skeletal muscle were lower while glucose oxidation was increased (P < 0.05). In subjects with NIDDM, proportions of type I, IIa, and IIb fibers were 37 +/- 2, 37 +/- 6, and 26 +/- 5%, respectively, which did not differ from nondiabetics; and capillary density, glycolytic, and aerobic-oxidative potentials were similar. During 6 h after ingestion of a mixed meal, arterial FFA remained greater in NIDDM subjects. Therefore, despite persistent reduced fractional extraction of oleate across the leg in NIDDM (0.34 +/- 0.04 vs. 0.38 +/- 0.03, P < 0.05), rates of oleate uptake across the leg were greater in NIDDM (54 +/- 7 vs. 45 +/- 8 nmol/min, P < 0.01). In summary, during postabsorptive conditions there is reduced utilization of FFA by muscle, while during postprandial conditions there is impaired suppression of FFA uptake across the leg in NIDDM. During both fasting and postprandial conditions, NIDDM subjects have reduced rates of lipid oxidation by muscle.